Migration and Remittances during the Global Financial Crisis and Beyond - Sirkeci, Ibrahim (Washington, DC: World Bank, 2013)
Immigrants tend to be more negatively affected by economic crisis than natives, particularly when governments apply strict immigration controls. With the onset of the financial crisis in the latter half of 2008, there were widespread concerns: would migrants return to sending countries and communities in large numbers, adding further economic woes to countries already facing difficulties? Would remittance flows slow and potentially cease? The literature offers little guidance on these questions. It is always a challenge to collect data, analyze, interpret, and make recommendations as the phenomenon under study is still unfolding to reveal new turns and twists. The most recent financial crisis and its repercussions are yet to be completed, and scholars have only begun processing the event. This volume is an effort to bring together in one place fresh thinking and evidence from around the world on the outcomes of mobility in the context of global financial crisis. This book is perhaps the first comprehensive study of remittances during the financial crisis and is a timely addition to the literature. It comes at a time when countries are grappling with the global financial crisis and it's after effects. The resilience of remittances is good news for developing countries, but leveraging remittances for socioeconomic development remains a key challenge. The studies in this book identify and discuss key patterns observed in remittance practices across the world and possibilities for the future.